1999
DOI: 10.3109/13550289909029475
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytes as targets for Venezuelan equine encephalitis virus infection

Abstract: Venezuelan equine encephalitis virus (VEE) produces an acute infection in humans and induces a well-characterized cytopathic effect in neurons of the central nervous system (CNS). However, little is known about the role of glial cells in response to VEE infection of the CNS. Our results demonstrate that VEE is capable of a productive infection in primary astrocyte cultures and that this infection is cytotoxic. Further, there were signi®cant differences in the growth kinetics comparing virulent and attenuated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 67 publications
4
40
1
Order By: Relevance
“…While NO clearly has antiviral activities, a high level of NO is toxic to neurons, and its antiviral effects can also be virus specific [206]. Consistently, high levels of NO was correlated with accelerated death in mice infected with VEEV [186], and its inhibition prolonged survival time in TBEV-, MVEV-, and VEEV-infected mice [204,206,207]. Alternatively, inflammatory responses can result in formation of reactive oxygen species, which, in turn, triggers neuronal death.…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 85%
See 1 more Smart Citation
“…While NO clearly has antiviral activities, a high level of NO is toxic to neurons, and its antiviral effects can also be virus specific [206]. Consistently, high levels of NO was correlated with accelerated death in mice infected with VEEV [186], and its inhibition prolonged survival time in TBEV-, MVEV-, and VEEV-infected mice [204,206,207]. Alternatively, inflammatory responses can result in formation of reactive oxygen species, which, in turn, triggers neuronal death.…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 85%
“…Activated astrocytes and microglia play an important role in inflammatory responses during natural infection with encephalitic flaviviruses, namely JEV [200], WNV [201], and TBEV [198], as well as encephalitic alphaviruses [186]. Upon activation, astrocytes and microglia release several chemokines and cytokines such as TNF-α, IL-6, C-X-C motif chemokine ligand (CXCL)10, chemokine (C-C motif) ligand 2, monocyte chemoattractant protein-1, RANTES, IFN-γ-induced protein 10, and matrix metalloproteinases [154,195,[202][203][204]. Elevated levels of matrix metalloproteinases disrupts BBB by degrading TJ proteins [203,205], allowing unrestricted entry of leukocytes into the brain, which further exacerbates neuroinflammation.…”
Section: Neuropathogenesis Of Arbovirusesmentioning
confidence: 99%
“…Previous studies have demonstrated that the murine model is characterized by biphasic disease, which starts with the productive infection of lymphoid tissue and ends in the destruction of the CNS by viral replication and a "toxic" neuroinflammatory response (12,13,15,16,39,42,43). By the time encephalitis has developed in an infected mouse, the infectious virus is usually absent from the peripheral organs and blood (12,13,15,16,39,42,43). However, virus replicates to high titers in the brain, and mice die 5 to 7 days after infection due to fatal encephalitis, as previously demonstrated with ZPC738 (2, 31).…”
Section: Discussionmentioning
confidence: 99%
“…In general, the main target cells for alphavirus infection in the CNS are neurons, but infection of astrocytes by VEE also has been described (10,21,50). To determine the target cell for VEE in the CNS, we inoculated eGFP-VRP i.c.…”
Section: Discussionmentioning
confidence: 99%